ON THE CONCEPT AND CLASSIFICATION OF ORGANIZED FORMS OF COMPLICITY IN CRIME - Apienov, S. M.; Makarenko, T. D.; Makisheva, M. K.; Umbetbayeva, Zh. B. (Farabi Journal of Social Sciences, 2018)
This paper considers one of the problems of the General part of Criminal law, the issues of classification of forms of complicity and the degree of correspondence of the current legislative formulation to the theoretical and practical requirements of Criminal law. The purpose of this article is to study the issues of classification of forms of complicity, the analysis of the legislation of the Republic of Kazakhstan on their compliance with the theoretical and practical requirements of the science of criminal law, as well as the proposal of the author’s scientific definition of organized forms of complicity. The scientific and practical significance of the work in the fact that in the theory of criminal law and law enforcement practice of our state and post-Soviet countries in general, one of the unresolved and debatable problems today is the distinction and identification of the most distinctive features of organized forms of complicity to the crime. The research methods for studying this problem are the historical, comparative legal, logical and structuralfunctional methods of scientific cognition. The main results and analysis, the findings of the research. The authors, drawing attention to the provisions of articles 31, 264 and 265 of the Criminal Code of the Republic of Kazakhstan, which establish the criminal responsibility for the creation and management of a transnational organized group, a transnational criminal organization, as well as the participation in them and the creation and management of a transnational criminal community and involvement in it, recognize the norms of articles 264 and 265 of the Criminal Code of the RK as superfluous. The reason for this assessment is the United Nations Convention against Transnational Organized Crime of 13 December 2000, which does not deal with the transnational nature of organized crime as an independent form of complicity. This document calls for international cooperation in combating organized criminal manifestations of an international character. According to the authors, a transnational organized group, a transnational criminal organization and a transnational criminal community are recognized as independent forms of complicity if these terms represent “a way to realize a criminal plan in the form of joint criminal offense”, which means the distinction between the forms of complicity in the science of criminal law. The practical significance of the results of the research of the problem under consideration lies in the fact that the materials of a scientific article can be used for further research in this area, used in the educational process, in legislative activities that regulate issues related to the institution of complicity. Key words: criminal law, form of complicity, a lower class, criminal community, criminal group